An Octave/MATLAB® Interface for Rapid Processing of SMOS L1C Full Polarization Brightness Temperature. Issue 1 (29th November 2017) - Saavedra, Pablo; Simmer, Clemens
A tool to process the SMOS microwave radiometer level 1C polarized brightness temperatures data product has been developed. The SMOS L1C science product contains the dual and full (Stokes vector) polarization brightness temperatures at L-band for multiple incidence angles. In order to use the L1C product, the measurements are processed by a number of procedures including radio frequency interference (RFI) filters, conversion of the polarization plane from the antenna (X- & Y-pol) to the Earth's surface frame (H- & V-pol), and averaging to fixed classes of incidence angles. The software allows for the processing of data for the entire daily half-orbit product, or for specific regions of interest, and can be adapted as a bash-job to process a large number of data files e.g. for time series analysis. This paper describes the tool which was developed in GNU C++ with the capability to be compiled as MEX function to work with Octave or MATLAB® without any source code adjustment.